Sustainability Strategy for Organic Rice Agribusiness Development in Banggai Regency - Bakri Muala; Made Antara; Alimudin Laapo; Effendy Effendy; Hadayani Hadayani (Postgraduate, University of Mataram, 2024)
The solution to reduce the negative impact of inorganic farming is to change to organic farming. The definition of organic farming is an agricultural cultivation system that uses natural organic materials. This study aims to analyze the level of sustainability of organic rice development in the social, economic, ecological, technological and infrastructure dimensions, governance and farmer ethics and develop a prioritization strategy for the sustainability of organic rice business development in Banggai Regency. The number of samples was 47 respondents. The data analysis method uses the RAP (Rapid Appraisal) method while for the determination of sustainability strategy decisions using SWOT Analysis and AHP. The results showed that the level of sustainability of the ecological, economic, social, technological and infrastructure dimensions, ethics and morals showed quite sustainable, and the development dimension showed very sustainable. Strategy selection is in quadrant I (IFAS 1.507 and EFAS 2.266) by focusing on aggressive growth in the development of sustainable organic rice agribusiness with strategic steps, namely: Optimizing organic rice production through the use of production input subsystems; optimizing extension activities in company-assisted farmer groups, inviting non-organic rice farmers to join the organic rice agribusiness business, expanding paddy fields to increase organic rice production, optimizing promotional activities for organic rice products, maintaining the quality of organic rice, making Sinorang Village and Sumberharjo Village into Organic Rice Agrotourism Villages, improvement and modification of organic rice packaging, provision of RMU assistance, and agricultural machinery equipment and developing self-reliance of organic rice farmer groups.